The gladiator - Scarrow, Simon (Scarrow, Simon, 2014)
Macro and Cato return to Rome after a campaign against the Parthians. Landing in Crete after their ship is almost capsized by a tidal wave they discover an earthquake has struck the island. In the aftermath with the slaves revolting, the governor calls on Macro and Cato to quell the rebellion.